2004
DOI: 10.1111/j.1349-7006.2004.tb03194.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of EPHA2 overexpression with high microvessel count in human primary colorectal cancer

Abstract: Evidence suggests that the erythropoietin-producing hepatocellular (EPH) receptor tyrosine kinases (RTKs) and their ephrin (EFN) ligands are involved in human carcinogenesis. Expression of two of them, EFNA1 ligand and its receptor, EPHA2, has been proposed to contribute to tumor-induced neovascularization. Colorectal cancers were examined for expressions of EPHA2 and its ligand EFNA1 by semi-quantitative RT-PCR, and double-immunostained for EPHA2 and CD34. Microvessels in the tumors were counted. Double-stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 35 publications
6
84
1
Order By: Relevance
“…The upregulation of the expression of several members of the Eph family of receptor tyrosine kinases has been reported (Easty et al, 1999;Liu et al, 2002;Miyazaki et al, 2003;Fox and Kandpal, 2004). We previously reported that EPHB2 is overexpressed in gastric cancer (Kiyokawa et al, 1994;Kataoka et al, 2002) and that EphA2 is overexpressed in colorectal cancer (Kataoka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upregulation of the expression of several members of the Eph family of receptor tyrosine kinases has been reported (Easty et al, 1999;Liu et al, 2002;Miyazaki et al, 2003;Fox and Kandpal, 2004). We previously reported that EPHB2 is overexpressed in gastric cancer (Kiyokawa et al, 1994;Kataoka et al, 2002) and that EphA2 is overexpressed in colorectal cancer (Kataoka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They also play a role in angiogenesis (Favre et al, 2003;Sullivan and Bicknell, 2003). In recent years, some of the Eph genes have been found to be overexpressed in human tumors, including neuroblastoma (Tang et al, 1999), lung carcinoma (Tang et al, 1999), gastric cancer (Kiyokawa et al, 1994;Kataoka et al, 2002), esophageal cancer (Miyazaki et al, 2003), breast cancer (Wu et al, 2004), and colorectal cancer (Stephenson et al, 2001;Liu et al, 2002Liu et al, , 2004Kataoka et al, 2004). Among the Eph family genes, relatively less attention has been directed toward EphA7 in human tumors, and the potential role of EphA7 in human oncology has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,6 For oncology applications, interest in EphA2 has grown recently due to its increased expression in most cancers including lung, breast, ovary, prostate, colorectal, skin and esophagus. [7][8][9][10][11][12][13] Interestingly, EphA2 is located on chromosome 1p36.1, which is a hotspot for rearrangements in many human cancers including ovarian cancer. [14][15][16] We have previously demonstrated that EphA2 is overexpressed in 76% of epithelial ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 In intestinal neoplasia, EphA2 has been reported to be up-regulated in human colorectal cancers, and EPHA2 overexpression correlates with colon cancer metastasis and high microvessel count in primary human colorectal cancers. [47][48][49] Ephrin A1 is also implicated in intestinal cancer. EFNA1 antisense oligonucleotides inhibited the growth of HT29 colon carcinoma cells, 50 and overexpression of murine Ephrin-A1 enhanced tumor multiplicity and tumor progression in Apc Min/1 mice.…”
mentioning
confidence: 99%